2017
DOI: 10.1080/23743603.2017.1327178
|View full text |Cite
|
Sign up to set email alerts
|

Power vs. persuasion: can open body postures embody openness to persuasion?

Abstract: In the current study we sought to replicate the finding that adopting an open/expansive body posture increases subjective feelings of power (Carney, Cuddy, & Yap, 2010), while also investigating how these body postures influence the processing of persuasive messages. Two hundred participants were randomly assigned to adopt either an open or a closed body posture while reading either a strong or a weak persuasive message regarding junk food taxation.Afterwards, we measured participants' attitudes towards junk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In addition, after engaging in HPPs, participants judged the weight of boxes to be lighter than participants did after engaging in LPPs (Lee & Schnall, 2014). No effects were found on thought confidence, persuasion, or openness (Latu, Duffy, Pardal, & Alger, 2017).…”
Section: Effects On the Actormentioning
confidence: 98%
“…In addition, after engaging in HPPs, participants judged the weight of boxes to be lighter than participants did after engaging in LPPs (Lee & Schnall, 2014). No effects were found on thought confidence, persuasion, or openness (Latu, Duffy, Pardal, & Alger, 2017).…”
Section: Effects On the Actormentioning
confidence: 98%
“…In 2015, a large-scale replication project [20] re-opened the files on 100 published experiments and found that a considerable number of reported effects did not replicate, leading to the so-called "replication crisis" in Psychology. Neither the study by Carney et al [14] nor the one by Yap et al [65] was among the replicated studies, but multiple high powered and pre-registered studies have since then failed to establish a link between power poses and various behavioral measures [53,30,43,55,1,8,38,47,44]. While a Bayesian meta-analysis of six pre-registered studies [34] provides credible evidence for a small effect of power poses on self-reported felt power (d ≈ 0.2), the practical relevance of this small effect remains unclear [41].…”
Section: Introductionmentioning
confidence: 99%
“…They did not replicate the basic power pose effect. • Latu, Duffy, Pardal, and Alger (2017) tested an interesting dependent variable in the context of power poses, persuasive messages. They did not observe any effect of power poses on persuasive message perception.…”
mentioning
confidence: 99%